Comparison of Postural Drainage and Percussion Techniques in Cystic Fibrosis Patients - Shah, Shahzaib Raza; Hassan, Zainab; Waqas, Shoaib; Ali, Aadil Ameer; Hamza, Makhdoom Muhammad (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the effects of postural drainage and percussion techniques in patients with cystic fibrosis. Methods: This research was carried out in the ‘South Punjab Clinics, Hospital Multan’ as a randomized clinical trial. From December 2020 to June 2021, the research was completed in about six months. This study used a sample size of 32 cystic fibrosis patients to determine the effects of postural drainage and percussion treatments. Two groups of patients were formed. Suctioning and aerosol medicines were used as a common treatment for both groups. Postural drainage, aerosol drugs, and suctioning were used in Group A, while the percussion method, aerosol medications, and suctioning were used in Group B. The frequency of sputum, forced spirometry FEV1 and patient satisfaction are also used. Results: The mean age and standard deviation of 32 patients was 281.009, including 20 males and 12 females. The pretreatment mean value of forced expiratory volume (FEV1) for the percussion and postural drainage groups was 4.25 and 2.38, and the post-treatment mean value was 1.00 and 2.22 respectively. The pretreatment mean value of sputum production for the percussion and postural drainage groups was 1.00 and 1.00, and the post treatment mean value was 2.25 and 2.19 respectively. Data was not normally distributed, so a non-parametric test (Mann-Whitney) was applied. The calculated p value was greater than 0.05. Conclusion: In cystic fibrosis patients, there was no substantial difference in the benefits of percussion and postural draining techniques.